Formação de usuários no arquivo judicial da Justiça Federal na Paraíba - Silva, Larissa Fernandes da (2019)
Institutions and information units that have as purpose to grant access to information and perform their activities aimed at users, need to perform training actions for users, both internal users who organize documents and external users who wish to access them. Considering that the studies of users and, more precisely, the studies of user training are still little explored, a research was carried out whose general objective is to analyze the user training activities in the judicial file of the Federal Court in Paraíba. This is a descriptive research and quantitative-qualitative approach. The methodological procedures include a bibliographical research, on the subjects Science of Information and Archivology, Studies of Users and Competence in Information and Training of Users subjects that provide theoretical support to the research, and a field research, realized in the Judicial File of the Federal Justice of the Paraíba of the João Pessoa Section. The study population corresponded to 51 users, 20 of whom were internal to the institution and 31 external users. The data collection instrument applied was a questionnaire that includes open and closed questions and consists of two parts: the first to identify the profile of users and the second to verify user training activities and access and search procedures of information. The obtained data were analyzed and interpreted, systematizing them by electronic tabulation. For the analysis of the open questions we adopted the Content Analysis of Bardin (2009). The survey confirmed that there is no formal and standardized user education program, whether internal or external. Only instructions are passed orally to the first and by telephone to the seconds when they contact the JFPB. It also ratified the need to carry out user training activities in the JFPB judicial file. From the data analyzed and the literature review, we developed guidelines for the implementation of a user training program at the JFPB. It is concluded that the practical actions of training of users, currently, are expanding from the active use and implantation of the systems so that the users know how to use them and to obtain the information that they desire. This is the new activity that the archivist and all information professionals must exercise, mainly due to the institutions' anxiety to perform the digitization of their collections.